Archive Documents as Technical and Cultural Instruments - Tozzo, Silvano (European Journal of Applied Sciences, 2023)
The object of this analysis is acts and documents produced through activities connected to the management of university building patrimony. Their evaluation as functional instruments - both from the context in which they originate and the conservative phase in which they are destined to when they are no longer effective - passes across some examples extracted from the literature related to archives. Some citations are utilized as a pretext to reflect on what could be defined as the features, or even properties, of the material preserved.